Photoprotection and its implications for drug safety - Kryczyk-Poprawa, Agata; Czarnecki, Grzegorz; Jaśkiewicz, Katarzyna (Medycyna pracy, 2024)
Appropriate photoprotection plays a key role in the safety of using medicinal preparations whose active substances may induce photosensitivity reactions. This aspect applies not only to drugs applied topically to the skin, but also systemically. Drug-induced photosensitivity reactions to light depend on the active substance contained in the medicinal product and its dose, which translates into the concentration in the skin, the type of ultraviolet radiation, its intensity and exposure time. The chemical structure of phototoxic drugs contains unsaturated chemical bonds and aromatic groups, which are responsible for the absorption of radiation, the formation of degradation products and/or free radicals and hypersensitivity reactions. Therefore, in order to prevent hypersensitivity reactions, it is necessary to use appropriate sun protection and/or avoid exposure to solar radiation during pharmacotherapy with selected groups of drugs. The paper presents the latest research results on the impact of drug-induced photohypersensitivity on the increased likelihood of skin cancer. Drugs with the potential to induce photohypersensitivity reactions are discussed, including information on the relationship between their long-term use and the incidence of skin cancer. Based on the data contained in the Product Characteristics, exemplary indications regarding the appropriate photoprotection method to ensure the safe use of the medicinal product are presented. Med Pr Work Health Saf. 2024;75(5).